ANALYSIS OF THE DISTRIBUTION AND COURSE OF ODONTOGENIC PHLEGMONS OF MAXILLOFACIAL LOCALIZATION - Lokes, K.P.; Polishchuk, S.S.; Ivanytska, O.S.; Voloshyna, L.I.; Steblovskyi, D.V.; Yatsenko, P.I.; Skrypnykov, P.M. (World of Medicine and Biology, 2024)
Despite the rapid development of stomatological science, the problem of the spread of purulent-necrotic diseases remains relevant. An analysis of patient cases histories of the maxillofacial surgery department of Poltava Regional Clinical Hospital named after M.V. Sklifosovsky for the period from 2018 to 2023. Among all patients of the department of maxillofacial surgery, the share of patients with maxillofacial phlegmons in different months ranged from 9 % to 32 %, with average annual indices from 12.0 % to 16.2 %. Depending on the localization, the following were most often affected: submandibular area in 59.8 % of cases; pterygomandibular space – 18.7 % of cases; submasseteric space – 8.8 % of cases; buccal area – 4.2 % of cases; floor of the oral cavity – 20.5 % of cases; phlegmon of the neck – 2.6 % of cases. The COVID-19 pandemic led to a certain increase in the number of such patients and a slight extension of the length of stay in hospital treatment.
Keywords: odontogenic phlegmon; maxillofacial localization; inflammatory process; intoxication; complex treatment